Exploring the Potential of Wayang Beber Remeng Mangunjaya’s Creative Industry to Develop a Cultural-Educational Tourism Village - Tirto Suwondo; Ahmad Zamzuri; Dessy Wahyuni; Nurweni Saptawuryandari; Yohanes Adhi Satiyoko; Dewanto Sukistono; Hariyanto, Hariyanto (Universitas Negeri Semarang, 2025)
This research aims to identify wayang beber (stretch sheet of paper with episodes of wayang painting) Remeng Mangunjaya's creative industry potential to create a cultural-educational tourism village. Researchers use an advocacy and participatory research paradigm, as well as textual, transformational, and hermeneutic phenomenology methodologies. Researchers conducted the study at Gelaran 2, located in Bejiharjo Village, Karangmojo Sub-district, Gunungkidul Regency, where wayang beber is preserved. Eleven research participants who were emotionally, structurally, and professionally connected to wayang beber and the culture-based tourism sector were involved in gathering the data through observation, interviews, and group discussions. The analysis applied descriptive-qualitative methodologies, design (creation), and interpretative phenomenological analysis (IPA). This study revealed that Wayang Beber Remeng Mangunjaya has a high potential for growth into creative industry products (publishing, multimedia, fashion, crafts, cuisine, etc.) and provides a solid foundation for developing a cultural-educative tourism village. The outcomes of this study can help stakeholders who are concerned about improving the community's economic well-being through culture-based tourism villages.